PERANAN IBU RUMAH TANGGA PADA PROGRAM KAWASAN RUMAH PANGAN LESTARI DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Atmadja, M Yogi Hadi; Rangga, Kordiyana K; Listiana, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The aims of this research are to determine the level of housewives rolein the KRPL Program and factors that related to the role of housewives in the KRPL Program. This research was conducted in December 2017 to January 2018 in Natar Sub - District, South Lampung District. The research used survey method in which respondents were housewives who implemented the KRPL Program in Pancasila Village and Sidosari Village as many as 40 people. Research data was analyzed descriptively and by Rank Spearman analysis test. The results of this research showed that the role of housewives in the KRPL Program were classified as high level. This was approved by the high role classification in tillage, planting, plant maintenance, harvesting, and marketing product.Key words: housewives, role, sustainable food home area program